Sickness and healing in Mark - van Eck, E. (Neotestamentica, 1993)
This article constitutes an attempt to analyse Jesus' healings and exorcisms in Mark from a social scientific perspective. Attention is given to sickness, healing and demon-possession as understood in the first-century Mediterranean world. In this regard, attention is given to the important difference between, on the one hand, disease and curing, and on the other, illness and healing. It is further postulated that Jesus' 'miracles' in Mark, regarding sick or demon-possessed people, should be understood as at least healings. By healing ill and demon- possessed people, Jesus not only declared them clean, but also reinstated them as part of the community. However, by means of this activity, the Marcan Jesus was also restoring the kingdom of God by creating a new household as symbol thereof.